Kajian Angka Bebas Jentik (ABJ) pada Dataran Tinggi di Kelurahan Kemiling Bandar Lampung - Helina Helmy; Rizki Agung Desiantoro (STIKES Columbia Asia Medan, 2024)
Dengue Fever is caused by the dengue virus transmitted by humans through the bite of Aedes aegypti and Aedes albopictus mosquitoes previously infected with dengue virus from other dengue fever patients. The problem is that there is no vaccine or anti-viral drug for dengue hemorrhagic fever, an extraordinary event of dengue hemorrhagic fever if in the community: someone dies or the mortality rate is fifty percent of the previous one and in one month the number of dengue cases doubles from the previous year. Epidemiological control of the presence of mosquitoes through the 3M movement and the larva-free rate (ABJ) ≥ 95% of the national target. Alternative Fogging is carried out if three or more patients with unexplained fever are found and more than or equal to five percent of larvae are found. Therefore, it is necessary to observe the larval stage of DHF vectors to determine the distribution, mosquito density, the main habitat of larvae, and the alleged risk of transmission. The purpose of this study was to determine the House Index, Container Index, Bruteau Index, Density Figure and ABJ through a larval survey. The sampling technique used proportional random sampling. Research instruments: questionnaires, observation sheets, flashlight equipment to check for the presence of larvae. Results HI, BI and CI Habitat Index > 5%. The larva free rate in Sumberejo Prosperous Village was 87%, indicating a moderate density of potential dengue transmission, because it was below > 95%.